ANALISIS SUMBER DAYA MANUSIA LULUSAN ALUMNI SEKOLAH TINGGI PENERBANGAN INDONESIA GUNA MENDUKUNG KESELAMATAN PENERBANGAN DI BANDAR UDARA CAKRABHUWANA – CIREBON - Pribadi Asih (Politeknik Penerbangan Indonesia Curug, 2018)
Analysis study of human resources graduates of Indonesian Aviation College, this study aims to obtain information with the facts in the field of human resources graduates of STPI, so that STPI graduates meet according to the needs at Cirebon Cakrabhuwana Airport, are there obstacles in fulfilling the needs of STPI graduates. To achieve this goal, descriptive research and observation research methods in the field are used. In this study, where the research describes a situation that is accompanied by a clear analysis of STPI graduate human resources with existing data and problems, by providing conclusions and suggestions